Facile synthesis of nanorods of tetragonal barium titanate using ethylene glycol. Issue 4 (May 2015) - Inada, Miki; Enomoto, Naoya; Hayashi, Katsuro; Hojo, Junichi; Komarneni, Sridhar
Abstract: Tetragonal barium titanate (BaTiO3 ) nanorods were synthesized from hydroxide precursor by a hydrothermal/solvothermal method with 10 vol% ethylene glycol as solvent. The hydroxide precursor slurry was prepared by the addition of 10 M NaOH to a mixed solution of BaCl2 and TiCl4 . When the above aqueous slurry was heated with water only at 200 °C, cubic BaTiO3 nanocrystals formed, whereas tetragonal BaTiO3 nanorods were obtained when heated with 10 vol% ethylene glycol. The crystallization of cubic BaTiO3 via dissolution–reprecipitation of precursor could be suppressed by the addition of ethylene glycol, resulting in the formation of tetragonal BaTiO3 under hydrothermal treatment at 200 °C.